Age-Related Increase in Skull Vibration-Induced Nystagmus Slow-Phase Velocity in a Clinical Population with Normal vHIT and VEMP: A Retrospective Cross-Sectional Analysis - Melissa Blanco-Pareja; Ruth Escudero-Medina; Nicolás Pérez-Fernández (Audiology Research, 2026)
Background/Objectives: Skull vibration-induced nystagmus (SVIN) is a reproducible marker of vestibular asymmetry, but its relationship with age in patients with normal conventional tests remains unclear. We evaluated whether age is associated with the presence of SVIN and with its slow-phase velocity (SVIN-SPV). Methods: In this retrospective cross-sectional analysis, 164 patients with dizziness or vertigo and normal video head impulse test (vHIT) and VEMPs were studied (107 SVIN-positive, 57 SVIN-negative). Logistic regression tested whether age predicted SVIN positivity; among the 107 positive patients, SVIN-SPV was analyzed by correlation and multivariable linear regression. Results: Age did not predict a positive SVIN (odds ratio 1.01 per year, p = 0.28), whereas male sex did (odds ratio 2.31, p = 0.02). Among positive patients, mean SVIN-SPV was 3.0°/s and correlated with age (r = 0.25, p = 0.009); age was the only significant covariate in multivariable regression (β = 0.035°/s per year, p = 0.010), and patients aged ≥60 years showed higher SVIN-SPV (p = 0.028). Conclusions: Thus, age was not associated with whether SVIN was present but with its intensity once present, compatible with possible age-related changes in vestibular asymmetry or central compensation, although the underlying mechanism was not directly assessed; these findings should not be generalized to physiological vestibular aging.